Validation and reproducibility of cardiovascular 4D-flow MRI from two vendors using 2 × 2 parallel imaging acceleration in pulsatile flow phantom and in vivo with and without respiratory gating. (March 2019) - Bock, Jelena; Töger, Johannes; Bidhult, Sebastian; Markenroth Bloch, Karin; Arvidsson, Per; Kanski, Mikael; Arheden, Håkan; Testud, Frederik; Greiser, Andreas; Heiberg, Einar; Carlsson, Marcus
Background: 4D-flow magnetic resonance imaging (MRI) is increasingly used. Purpose: To validate 4D-flow sequences in phantom and in vivo, comparing volume flow and kinetic energy (KE) head-to-head, with and without respiratory gating. Material and Methods: Achieva dStream (Philips Healthcare) and MAGNETOM Aera (Siemens Healthcare) 1.5-T scanners were used. Phantom validation measured pulsatile, three-dimensional flow with 4D-flow MRI and laser particle imaging velocimetry (PIV) as reference standard. Ten healthy participants underwent three cardiac MRI examinations each, consisting of cine-imaging, 2D-flow (aorta, pulmonary artery), and 2 × 2 accelerated 4D-flow with (Resp+) and without (Resp−) respiratory gating. Examinations were acquired consecutively on both scanners and one examination repeated within two weeks. Volume flow in the great vessels was compared between 2D- and 4D-flow. KE were calculated for all time phases and voxels in the left ventricle. Results: Phantom results showed high accuracy and precision for both scanners. In vivo, higher accuracy and precision ( P < 0.001) was found for volume flow for the Aera prototype with Resp+ (–3.7 ± 10.4 mL, r = 0.89) compared to the Achieva product sequence (–17.8 ± 18.6 mL, r = 0.56). 4D-flow Resp− on Aera had somewhat larger bias (–9.3 ± 9.6 mL, r = 0.90) compared to Resp+ ( P = 0.005). KE measurements showed larger differences between scanners on the same day compared to the same scanner at different days. Conclusion: Sequence-specific in vivo validation of 4D-flow is needed before clinical use. 4D-flow with the Aera prototype sequence with a clinically acceptable acquisition time (<10 min) showed acceptable bias in healthy controls to be considered for clinical use. Intra-individual KE comparisons should use the same sequence.